2020
DOI: 10.1155/2020/5798764
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology‐Based Identification of the Mechanisms of Shen‐Qi Compound Formula in Treating Diabetes Mellitus

Abstract: Aim. The purpose of this research is to identify the mechanisms of Shen-Qi compound formula (SQC), a traditional Chinese medicine (TCM), for treating diabetes mellitus (DM) using system pharmacology. Methods. The active components and therapeutic targets were identified, and these targets were analyzed using gene ontology (GO) enrichment analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis, and protein-protein interaction (PPI) analysis. Finally, an integrated pathway was constructed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…e goal of this integrative science is to unveil the mechanisms of disease pathogenesis and drug activity that are coordinated through the interactions among diverse biological components such as genes, proteins, cells, tissues, and organs [61][62][63][64][65][66][67][68]. Previous network pharmacology studies successfully investigated the polypharmacological properties of herbal drugs by identifying their active compounds and key therapeutic targets and further elucidating the distinct system-level pharmacological effects and mechanisms (e.g., therapeutic modulation of biological processes such as proliferation, apoptosis, cell cycle regulation, angiogenesis, oxidation and reduction, insulin metabolism, and inflammation) for the treatment of various diseases, including cancer, diabetes, arthritis, and ischemic stroke, which are exerted by the synergistic interplay between multiple compounds and targets contained in herbal drugs [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. In the present network pharmacology study, we aimed to uncover the molecular mechanisms that underlie the analgesic properties of JGd with a system's perspective.…”
Section: Introductionmentioning
confidence: 99%
“…e goal of this integrative science is to unveil the mechanisms of disease pathogenesis and drug activity that are coordinated through the interactions among diverse biological components such as genes, proteins, cells, tissues, and organs [61][62][63][64][65][66][67][68]. Previous network pharmacology studies successfully investigated the polypharmacological properties of herbal drugs by identifying their active compounds and key therapeutic targets and further elucidating the distinct system-level pharmacological effects and mechanisms (e.g., therapeutic modulation of biological processes such as proliferation, apoptosis, cell cycle regulation, angiogenesis, oxidation and reduction, insulin metabolism, and inflammation) for the treatment of various diseases, including cancer, diabetes, arthritis, and ischemic stroke, which are exerted by the synergistic interplay between multiple compounds and targets contained in herbal drugs [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. In the present network pharmacology study, we aimed to uncover the molecular mechanisms that underlie the analgesic properties of JGd with a system's perspective.…”
Section: Introductionmentioning
confidence: 99%
“…The bigger size the of the node, the higher the corresponding degree value. According to the degree value, top 10 genes that were found to be influential targets in the treatment of ZL capsule via ferroptosis are as follows: TP53 [ 25 ], TNF [ 23 ], EGFR [ 22 ], PTEN [ 22 ], MYC [ 21 ], JUN [ 21 ], PTGS2 [ 18 ], RELA [ 16 ], HMOX1 [ 15 ] and GSK3B [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…TCMSP is a database with the composition of herbal entries, which could help reveal the mechanisms of action of traditional Chinese medicine (TCM) and uncover the nature of TCM theory [ 22 ]. According to the characteristics of pharmacokinetics ADME (absorption, distribution, metabolism, and excretion), the results retrieved from TCMSP were screened by two indexes: oral bioavailability (OB) ≥30% and drug-likeness (DL) ≥0.18 to screen the effective active ingredients of ZL capsule [ 24 , 25 ]. The active ingredients of Shuizhi and Dilong were screened from TCMID ( https://47.100.169.139/tcmid/search/ ), and then screened in SwissADME to filter ingredients with low gastrointestinal (GI) absorption and SwissTargetPrediction [ 26 ] to predict the most probable protein targets [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…rough the upregulation of VEGF, NO, ROS, and PDGF, it is able to cause endothelial cell dysfunction, proliferation, angiogenesis, and inflammation [34]. It was also found that the TNF, PI3K/Akt, and MAPK signal pathways can interact with the HIF signal pathway, leading to the gradual progress of diabetes and its complications [35].…”
Section: Discussionmentioning
confidence: 99%